(untitled) (CAHIERS MAGELLANES-NS, 2024)
Design thinking has been adopted as an innovative technique across the disciplines in altering the way people approach problems and opportunities. This paper provides a systematic review that intends to understand the existing trends of design thinking as well as the studies on its effects, methods, uses, and potential developments in various fields. The flow of publications in the field is analyzed, citation patterns, and collaborations of authors working in the field of design thinking are studied. Thus, blending the quantitative analysis with the qualitative findings of the literature review, this research contributes to the understanding of the process of the transformation of design thinking from the niche activity to the paradigm that shapes the academic discourses and practical problem-solving practices. Exploring the research literature reveals the extent to which design thinking is capable of creating empathic value in solving multiple societal issues. This is mainly because of the methodological approach, especially the iterative model of ideation, prototyping, and testing that forms the building blocks of improving the innovation process. Such an approach not only fosters creativity and flexibility, but it also ensures that those creating solutions are not only thinking user-centric, but are also aligned with the user’s goals and desires. Some of the practical fields that have applied design thinking techniques include fields such as health, learning, management, and city design. Other successful examples disclosed how it contributes effectively to implementing organizational change and improving the users’ experience with the solutions that appeal to their needs. As for the future of this approach, design thinking research’s forecast looks bright and filled with opportunities for augmentation through artificial intelligence and virtual reality, which will refine its foresight and broaden its coverage on an international level. Therefore, based on this bibliometric analysis, it is clear that design thinking is an indispensable approach in today’ research paradigms. Thus, design thinking not only enriches students’ discursive practices but also promotes creative and effective solutions to real-life problems with the help of cooperation, empathy, and critical thinking.